The experience of tobacco withdrawal symptoms among current smokers and ex-smokers in the general population: Findings from nationwide China Health Literacy Survey during 2018-19 - Cui, Zi-yang; Li, Ying-hua; Liu, Zhao; Li, Li; Nie, Xue-qiong; Zhou, Xin-mei; Cheng, An-qi; Li, Jin-xuan; Qin, Rui; Wei, Xiao-wen; Zhao, Liang; Ladmore, Daniella; et al. (Frontiers in Psychiatry, 2023)
Objective: To clarify the extent to which smokers in the general population experience tobacco withdrawal symptoms and whether such experience differs in those who continue to smoke and those who stop smoking. Methods: We included relevant questions in the nationally-representative China Health Literacy Survey (CHLS) conducted in 2018-2019. Among 87,028 participants, there were 22,115 ever-smokers aged 20-69 years who provided information on their smoking history and their experience of tobacco withdrawal symptoms. Multivariate logistic regressions were conducted to explore the association between withdrawal symptoms and other variables. Results: Among ever-smokers, there were 19,643 (88.8%) current smokers and 2,472 (11.2%) ex-smokers. Among current smokers, 61.3% reported having tried to quit smoking in the past. Overall, 61.1% of current smokers reported experiencing withdrawal symptoms: 69.9% of those who tried to quit smoking in the past and 47.5% of those who did not. A lower proportion of ex-smokers experienced withdrawal symptoms (46.3%) and the difference remained significant after controlling for demographic characteristics (OR=1.77, 95%CI 1.62-1.93, P<0.0001). The most commonly-reported withdrawal symptoms in both current smokers and ex-smokers were craving, restlessness and anxiety. In the multivariable-adjusted analyses, those who experienced withdrawal symptoms when they quit smoking (OR: 2.05, 95% CI: 1.86-2.27) were less likely to successfully quit smoking (defined as being ex-smokers). Conclusions: Our study documents that tobacco withdrawal syndrome is common in adult smokers in the general population. As tobacco withdrawal syndrome is one of the key obstacles to smoking cessation, withdrawal-oriented therapy should be highly valued in tobacco cessation treatment in China and elsewhere.